Gender inequality in healthcare leadership: the challenges women face in breaking through the glass ceiling - Kiran Imtiaz Khan; Brekhna Jamil; Muhammad Muhammad; Shamaila Mohsin; Arsalan Hamid Khan; Muhammad Qasim Javed (BMC Health Services Research)
Abstract Background Women comprise more than two-thirds of the academic medicine faculty and half of the general population in Pakistan, yet their representation in healthcare leadership roles remains disproportionately low. Aim The study aims to explore the experiences of Pakistani women in healthcare leadership positions to unravel the challenges they face in acquiring and sustaining leadership positions and to identify the factors that help them overcome these challenges. Methods An exploratory qualitative study based on semi-structured interviews was conducted. Purposive sampling was utilized. Telephonic interviews of ten women in healthcare leadership positions were conducted, recorded, and transcribed. Thematic analysis was performed by manual coding. Results A total of 14 subthemes were generated that finally emerged as 5 themes. The challenges of women in healthcare leadership positions included unsupportive work environment, lack of confidence and leadership skills, and struggle to balance family and work. Personal strategies, family support, and women-centric organizational policies were identified as aids to professional advancement. Conclusion Most of the challenges faced by women in acquiring and sustaining leadership positions in Pakistan are rooted in a patriarchal culture that assigns conventional roles and expectations to women. Professional competence and strategic acumen along with inclusive work environment and policies can help promote gender equality.